Evaluation of human capital using the example of the chemical and petrochemical industry of the republic of Kazakhstan using the cobb-Douglas production function (Journal of Economic Research & Business Administration, 2023)
The issues discussed in this article are related to the development of a methodology for assessing the effectiveness of human capital at enterprises in the chemical (petrochemical) industry. The formation of the industry in the future also depends on the qualitative formation of human capital.The purpose of this study is to analyze and assess the effectiveness of human capital in the chemical and petrochemical industries of the Republic of Kazakhstan. There are various approaches to assessing the quality of human capital. The authors of the article assessed the effectiveness of the use of human capital on the example of the chemical and petrochemical industries of Kazakhstan using the Cobb-Douglas production function. In the framework of the study, the authors answer the question of the possibility of building an adequate Cobb-Douglas production function with dynamic parameters using the example of the chemical and petrochemical industries of the Republic of Kazakhstan for 2000–2020.The main characteristics of the production function were calculated, a comparative analysis of the efficiency of the use of labor resources and investments in various fields of the chemical and petrochemical industries was made. During the analysis, problems were identified in several areas of the chemical and petrochemical industries a decrease in labor productivity, a decrease in stock availability, and a return on investments, which has become especially noticeable since 2019. The value of the study is that the possibility of estimating human capital using the Cobb-Douglas function is shown. This methodic can be used not only for the chemical and petrochemical industries, but also for any other industry.Keywords: chemical and petrochemical industries, human capital, professional standards.